Exhaustive sampling of the fragment space associated to a molecule leading to the generation of conserved fragments. (12th December 2017) - Heikamp, Kathrin; Zuccotto, Fabio; Kiczun, Michael; Ray, Peter; Gilbert, Ian H.
Abstract : The first step in hit optimization is the identification of the pharmacophore, which is normally achieved by deconstruction of the hit molecule to generate "deletion analogues." In silico fragmentation approaches often focus on the generation of small fragments that do not describe properly the fragment space associated to the deletion analogues. We present significant modifications to the molecular fragmentation programmemolBLOCKS, which allows the exhaustive sampling of the fragment space associated with a molecule to generate all possible molecular fragments. This generates larger fragments, by combining the smallest fragments. Additionally, it has been modified to deal with the problem of changing pharmacophoric properties through fragmentation, by highlighting bond cuts. The modifiedmolBLOCKS programme was used on a set of drug compounds, where it generated more unique fragments than standard fragmentation approaches by increasing the number of fragments derived per compound. This fragment set was found to be more diverse than those generated by standard fragmentation programmes and was relevant to drug discovery as it contains the key fragments representing the pharmacophoric elements associated with ligand recognition. The use of dummy atoms to highlight bond cuts further increases the information content of fragments by visualizing their previous bonding pattern. Abstract : We report the modification of the programmemolBLOCKS to allow exhaustive fragmentation of molecules to generate all possible molecular fragments, including larger fragments and to cope with fragmentation occurring through key pharmacophoric groups. The programme was used to fragment a set of drug compounds, leading to an increased number of unique fragments per molecule, compared to standard algorithms.